2017
DOI: 10.3389/fmicb.2017.00766
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of Methanogenesis and Sulfate Reduction with Common Substrates in Sulfate-Rich Estuarine Sediments

Abstract: The competition between sulfate reducing bacteria and methanogens over common substrates has been proposed as a critical control for methane production. In this study, we examined the co-existence of methanogenesis and sulfate reduction with shared substrates over a large range of sulfate concentrations and rates of sulfate reduction in estuarine systems, where these processes are the key terminal sink for organic carbon. Incubation experiments were carried out with sediment samples from the sulfate-methane tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(98 citation statements)
references
References 64 publications
9
89
0
Order By: Relevance
“…Although the concave‐up shape of methane profile was often interpreted as the diffusion of methane from SMTZ, increasing evidence suggested endogenous methane production could occur in the sulfate‐rich sediments (Maltby et al ; Sela‐Adler et al ; Xiao et al ; Zhuang et al ), as observed in this study. Therefore, the low but detectable concentrations of methane could be a collective result of production, consumption, and diffusion from underlying sediment below SMTZ.…”
Section: Discussionsupporting
confidence: 57%
“…Although the concave‐up shape of methane profile was often interpreted as the diffusion of methane from SMTZ, increasing evidence suggested endogenous methane production could occur in the sulfate‐rich sediments (Maltby et al ; Sela‐Adler et al ; Xiao et al ; Zhuang et al ), as observed in this study. Therefore, the low but detectable concentrations of methane could be a collective result of production, consumption, and diffusion from underlying sediment below SMTZ.…”
Section: Discussionsupporting
confidence: 57%
“…Among the 10 HgcA sequences found in the gene ocean catalogue, none was affiliated to methanogenic Archaea . Even if the co-existence of methanogens and sulfate-reducers has been evidenced in marine sediments 24 , sulfate reduction usually outcompetes methanogenesis in seawater under non-limiting sulfate concentrations 25 . Our results thus show that Hg-methylators in the ocean span a large taxonomic diversity, not limited to sulfate-reducing bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…This supports the dominance of methylotrophic methanogenesis, which is over 90% of total CH 4 production rates at 0–2 cm and over 60% at other depths except for 2–4 cm. As the anoxic incubation condition excluded the possibility of aerobic CH 4 production from methylphosphonate (Karl et al ; Repeta et al ), the methylotrophic methanogenesis from methylated compounds appears to be the only possible explanation for such a difference (Sela‐Adler et al ). A large potential of this methanogenic pathway in the sediment was shown by slurry incubation experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Methane was measured by gas chromatography via a flame ionization detector (SRI 310C, SRI Instruments, U.S.A.). The isotope ratio of 13 C-CH 4 was determined by coupling a pre-concentration gas chromatograph (GC) with an isotope ratio mass spectrometer system (IRMS) (Thermo Fisher Scientific, Germany) (Rice et al 2001), and the same GC/IRMS without pre-concentration system was used for DIC measurement (Torres et al 2005). The Vienna Pee Dee Belemnite (VPDB) standard was used for the d 13 C values reference.…”
Section: Chemical Analysismentioning
confidence: 99%